The Application of Artificial Intelligence in Recruitment and Selection: Ethical Challenges and Effectiveness - Enis Sholikhah; Suharto Suharto; Rachmad Ilham (BADAN PENERBIT STIEPARI PRESS, 2025)
This study explores the application of Artificial Intelligence (AI) in recruitment and selection processes, focusing on its effectiveness and the ethical challenges it presents. Utilizing a qualitative method through a systematic literature review, the research examines recent scholarly works published in the last five years. The findings reveal that AI significantly enhances recruitment efficiency by streamlining candidate screening, improving job fit predictions, and reducing human bias. However, these advantages are counterbalanced by ethical risks such as algorithmic bias, lack of transparency, and potential infringements on candidate privacy. The analysis is grounded in the Resource Based View and Technology Acceptance Model, supported by deontological and utilitarian ethical frameworks. The study concludes that while AI offers strategic value in talent acquisition, its implementation must be ethically governed to ensure fairness and accountability. These insights offer theoretical contributions to HRM literature and practical guidance for organizations adopting AI in recruitment systems.